Identifikasi Sampah Anorganik di Pantai Cermin Desa Pantai Cermin Kanan Kecamatan Pantai Cermin Kabupaten Serdang Bedagai - Yudho Andika; Sohibil Yamin; Erlangga Erlangga; Syahrial Syahrial; Imamshadiqin (Faculty of Science and Technology University Ibrahimy, 2023)
Garbage is a major problem experienced on a global scale, both from household and industrial waste. This research was conducted at Pantai Cermin, Pantai Cermin Kanan Village, Pantai Cermin District, Serdang Bedagai Regency. It was carried out on 6-12 November 2021 with the aim of knowing the type, characteristics, weight, total density, and rate of increase in weight of inorganic waste. The method used is purposive sampling by installing a plot of 10 m x 10 m with a distance of each transect of 5 m. Data collection was carried out by observation with macro size and recorded directly. The results of the research show that the waste obtained is plastic, glass, rubber, clothing, metal / metal and the most dominant is plastic waste. The density of the number of pieces and the largest weight density in plastic waste are 0.31 items/m2 and 2.93 gr/m2. The highest rate of weight gain was on Sundays (r>0).